Shear-accelerated crystallization of glass-forming metallic liquids in high-pressure die casting. (1st August 2022) - Liu, L.H.; Gao, W.J.; Huang, X.S.; Zhang, T.; Liu, Z.Y.; Yang, C.; Zhang, W.W.; Li, W.R.; Li, L.; Li, P.J.
Highlights: Solidification behavior of Zr55 Cu30 Ni5 Al10 glass forming liquid under various flow rates was investigated. Flow-induced crystallization was observed in glass forming liquid as injection rate exceeds 1.1 m/s. The accelerated crystallization behavior is mainly ascribed to the abrupt perturbation at the end filling stage. Flow related effect on glass forming ability must be considered in bulk metallic glasses produced by high pressure die casting. Abstract: As one of the most important forming technologies for industrial bulk metallic glass (BMG) parts with complex shapes, high-pressure die casting (HPDC) can fill a die cavity with a glass-forming metallic liquid in milliseconds. However, to our knowledge, the correlation between flow and crystallization behavior in the HPDC process has never been established. In this study, we report on the solidification behavior of Zr55 Cu30 Ni5 Al10 glass forming liquid under various flow rates. Surprisingly, the resulting alloys display a decreasing content of amorphous phase with increase of flow rate, i.e. increase of cooling rate, suggesting that crystallization kinetics of glass-forming metallic liquids in the HPDC process is strongly dependent on the flow field. Analysis reveals that the accelerated crystallization behavior is mainly ascribed to the rapid increase in viscosity with a decreasing temperature as well as to the huge shear effect in the glass-forming liquid at the end stage of the filling process when the temperature is close to the glass-transition point; this results in a transition from diffusion- to advection-dominated transport. The current investigation suggests that flow-related crystallization must be considered to assess the intrinsic glass-forming ability of BMGs produced via HPDC. The obtained results will not only improve the understanding of crystallization dynamics but also promote the high-quality production and large-scale application of BMG parts.